The Influence of Business Ethics of Business Actors and Tourist Satisfaction on Revisit Decisions Mediated by Tourist Preferences in Malioboro, Yogyakarta in the New Normal Era - Ainiya, Sri Khusnul; Guritno, Bambang; Listyorini, Haniek (Media Wisata, 2024)
The application of the New Normal during the pandemic is very influential on the tourism sector, especially in Malioboro Yogyakarta. This study aims to describe and analyze the influence of Ethical Business Conducted and Tourist Satisfaction to decision of revisit in the Mediation of Tourists Preference at Malioboro Yogyakarta In the Era of the New Normal. This research used quantitative methods. The sample of this study which 100 tourists at Malioboro. Was taken by accidental sampling technique. The data were the analyzed by using a Multiple Linier Regresion Equation and sobel Test. The research concludes that : Ethical business conducted was positively and significantly influence on Tourist Preference, Tourist Statification was positively and significantly influence on Tourist Preference, Ethical business conducted was positively and significantly influence on the decision of revisit, Tourist Statification was positively and significantly influence on the decision of revisit, Tourist Preference was positively and significantly influence on the decision of revisit, Tourist Preference has no mediation to impact Ethical business conducted on the decision of revisit, Tourist Preference has no mediation to impact Tourist Statification on the decision of revisit.